الإعجاز العلمي في القرآن بين النصوص الشرعية والاكتشافات الحديثة: دراسة تحليلية Scientific miracles in the Quran: between religious texts and modern discoveries – an analytical study - Azimi, Rahmatullah; Rahmani, Shujauddin; Al-Khairabadi, Mohammed Abullais (IIUM Press, 2025)
تتناول هذه الدراسة تحليل مفهوم الإعجاز العلمي في القرآن الكريم وتسليط الضوء على العلاقة بين النصوص الشرعية والاكتشافات العلمية الحديثة، منطلقة من فرضية أن القرآن الكريم يتضمن إشارات علمية تعزز الإيمان، وتدعم البحث العلمي. تناولت الدراسة ثلاثة محاور رئيسية: مفهوم الإعجاز العلمي وأصوله الشرعية، والتحديات المنهجية التي تواجه تفسير النصوص، مثل التسرع والاعتماد على نظريات غير مستقرة، وأخيرًا تقديم أمثلة تحليلية تربط بين النصوص الشرعية والاكتشافات الحديثة. وخلصت الدراسة إلى أهمية المنهجية الدقيقة والمتوازنة التي تحترم النصوص الشرعية، وتجنب تحميلها تأويلات غير مبررة، مع دعوة لتعاون العلماء الشرعيين والعلميين لتحقيق فهم أعمق وشامل للإعجاز العلمي، يعزز التكامل بين الإيمان والعقل. This study aims to analyze the concept of scientific miracles in the Quran and highlight the relationship between religious texts and modern scientific discoveries. It is based on the premise that the Quran contains scientific references that strengthen faith and support scientific research. The study addresses three main areas: the concept of scientific miracles and their foundational principles, the methodological challenges in interpreting the texts, such as hastiness and reliance on unstable theories, and finally, providing analytical examples that link religious texts to modern discoveries. The study concludes by emphasizing the importance of a precise and balanced methodology that respects religious texts and avoids imposing unwarranted interpretations. It also calls for collaboration between religious scholars and scientists to achieve a deeper and more comprehensive understanding of scientific miracles, fostering integration between faith and reason.